Association between satisfaction with meaningful activities and social frailty in community-dwelling Japanese older adults. (May 2022) - Miyata, Hironori; Maruta, Michio; Makizako, Hyuma; Han, Gwanghee; Ikeda, Yuriko; Nakamura, Atsushi; Tokuda, Keiichiro; Shimokihara, Suguru; Akaida, Shoma; Hidaka, Yuma; Akasaki, Yoshihiko; Kubozono, Takuro; et al.
Highlights: This study examined the association between social frailty and meaningful activity. Social frailty is associated satisfaction with meaningful activities. The prevalence of social frailty can increase with a high aging rate. Engaging in satisfactory meaningful activities may decrease social frailty in older adults. Abstract: Objectives: This cross-sectional study investigates the associations among satisfaction with meaningful activities, and social frailty in community-dwelling Japanese older adults. Methods: We analyzed data from 596 older adults (mean age 74.2 ± 6.4 years, female 63.6%) who participated in the Tarumizu Study 2019, a community-based health survey. Participants selected meaningful activities from 95 activities using the Aid for Decision-Making in Occupation Choice (ADOC) tool. Satisfaction was evaluated from 1 to 5, and those who were assigned a rating of 4 or 5 were operationally classified as the high satisfaction group ( n = 487), with others occupying the low satisfaction group ( n = 109). Both groups were evaluated based on the ADOC, social frailty (Makizako's five items), physical function, depressive symptoms, cognitive function, and higher-level competence. Results: Of the 596 participants, 18.7% showed prevalence of social frailty. The low satisfaction group had a significantly higher prevalence of social frailty (low satisfaction 28.4% vs. high satisfaction 16.4%, P = 0.004) and depressive symptoms (low satisfaction 30.3% vs. high satisfaction 17.9%, P <0.01), and poor higher-level competence ( P = 0.026) than the high satisfaction group. Logistic regression analysis showed that social frailty (Odds Ratio 1.78, 95% Confidence Interval 1.068–2.990, P = 0.027) was significantly associated with satisfaction with meaningful activity after adjusting for covariates. We found no significant differences in categories of meaningful activities between the low and high satisfaction groups ( P = 0.549). Conclusions: This study suggested that social frailty was associated with satisfaction with meaningful activities, regardless of the degree or category of satisfaction.